Pengaruh Literasi Digital, Pendidikan Kewirausahaan, Dan Kompetensi Diri Terhadap Minat Berwirausaha Berbasis Digital - Rahman, Rahman (Edunomics Journal, 2024)
This study aims to determine the effect of digital literacy, entrepreneurship education, and self-competence on digital-based entrepreneurial interest of class XI students of SMKN 4 Palangka Raya. The research method used in this research is quantitative research method with descriptive approach. The source of data in this study is class XI students with a sample taken totaling 25 people. Based on the results of research on digital literacy variables, the significance value is obtained more <0.05, namely 0.041 <0.05, and the value of t count> t table, namely 5.904> 2.080, which means that the digital literacy variable affects digital-based entrepreneurial interest in class XI students of SMKN 4 Palangka Raya. On the entrepreneurship education variable has a positive and significant effect on interest in Digital-Based Entrepreneurship in class XI students of SMKN 4 Palangka Raya with the results of the analysis obtained of 0.000 <0.05, and the value of t count> t table is 13.345> 2.080. Furthermore, based on the value of the Coefficient of Determination (R Square) is equal to 0.899, meaning that the results above there is an influence of variables XI, X2 and X3 on variable Y by 89.9%, and the remaining 10.1% is influenced by other factors